56.4k views
4 votes
Find the inverse of the function f(x) = 2x² - 3x NO ABSURD ANSWERS IF YOU DON't WANT YOURSELVES TO GET REPORTED!

2 Answers

2 votes

Answer:


\boxed{f^(-1)(x)= (√(8x+9)+3)/(4)}

Explanation:


f(x)=2x^2-3x


f(x)=y


y=2x^2-3x

Switch variables.


x=2y^2-3y

Solve for y.

Multiply both sides by 8.


8x=16y^2-24y

Add 9 on both sides.


8x+9=16y^2-24y+9

Take the square root on both sides.


√(8x+9) =√(16y^2-24y+9)

Add 3 on both sides.


√(8x+9)+3 =√(16y^2-24y+9)+3

Divide both sides by 4.


(√(8x+9)+3)/(4)= (√(16y^2-24y+9)+3)/(4)

Simplify.


(√(8x+9)+3)/(4)= (4y-3+3)/(4)


(√(8x+9)+3)/(4)= (4y)/(4)


(√(8x+9)+3)/(4)=y

Inverse y =
f^(-1)(x)


f^(-1)(x)= (√(8x+9)+3)/(4)

User Alexandre Teixeira
by
5.2k points
6 votes

Answer:


f^(-1)(x) = (3)/(4) \pm (1)/(4)√(8x + 9)

Explanation:


f^(-1)(x) = 2x^2 - 3x

Change function notation to y.


y = 2x^2 - 3x

Switch x and y.


x = 2y^2 - 3y

Solve for y.


2y^2 - 3y = x

Complete the square on the left side. We must divide both sides by 2 to have y^2 as the leading term on the left side.


y^2 - (3)/(2)y = (x)/(2)

1/2 of 3/2 is 3/4. Square 3/4 to get 9/16.

Add 9/16 to both sides to complete the square.


y^2 - (3)/(2)y + (9)/(16) = (x)/(2) + (9)/(16)

Find common denominator on right side.


(y - (3)/(4))^2 = (8x)/(16) + (9)/(16)

If X^2 = k, then
X = \pm √(k)


y - (3)/(4) = \pm \sqrt{(1)/(16)(8x + 9)}

Simplify.


y = (3)/(4) \pm (1)/(4)√(8x + 9)

Back to function notation.


f^(-1)(x) = (3)/(4) \pm (1)/(4)√(8x + 9)

User Ashok
by
4.2k points